2020
DOI: 10.1371/journal.pone.0226098
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of chikungunya ECSA genotype and local outbreak in an upper medium class neighborhood in Northeast Brazil

Abstract: The chikungunya East/Central/South/Africa virus lineage (CHIKV-ECSA) was first detected in Brazil in the municipality of Feira de Santana (FS) by mid 2014. Following that, a large number of CHIKV cases have been notified in FS, which is the second-most populous city in Bahia state, northeastern Brazil, and plays an important role on the spread to other Brazilian states due to climate conditions and the abundance of competent vectors. To better understand CHIKV dynamics in Bahia state, we generated 5 complete g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In Brazil, the local transmission of the Asian lineage was detected for the first time in September 2014 in the Oiapoque city, Amapá state, North Region. Seven days later, a new cluster of CHIKV infections was notified in the city of Feira de Santana, Bahia state, Northeast Region [ 12 , 13 , 14 , 15 ]. Since then, the disease has spread across the country, posing a serious threat to public health.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the local transmission of the Asian lineage was detected for the first time in September 2014 in the Oiapoque city, Amapá state, North Region. Seven days later, a new cluster of CHIKV infections was notified in the city of Feira de Santana, Bahia state, Northeast Region [ 12 , 13 , 14 , 15 ]. Since then, the disease has spread across the country, posing a serious threat to public health.…”
Section: Introductionmentioning
confidence: 99%
“…To highlight the importance of investigating these variants, the ECSA genotype (East/Central/South African), when compared to the African genotype S-27 (S-27) in mice, caused a high and acute fatality, with a higher viral load in the central nervous system and peripheral organs [22]. This genotype has endured in northeastern Brazil, since its first detection in the country in 2014 [23], which shows concern about its circulation and its possible consequences on the population's health.…”
Section: Introductionmentioning
confidence: 99%
“…However, after the first years of expansion, these genotypes have been undergoing distinct transmission dynamics. While the AC genotype remained mostly restricted to the North region (13), the ECSA genotype is spreading widely and has been detected in all Brazilian states (9,12,14,15,17,1719). A recent study showed that the most affected region of Brazil was the Northeast (16), whereas limited CHIKF cases had been detected in the South region (20,43).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies characterizing these events suggested that both lineages would spread and cause outbreaks country-wide, with a higher transmission potential in the tropical region (8). This hypothesis was later corroborated with several Brazilian states in the North, Northeast, Southeast and Central-West regions experiencing large CHIKV outbreaks; whereas the South region experienced lower CHIKV incidence (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 88%